Health Care Providers’ Perceptions of the Ministry of Health’s Organizational Readiness for Change - Jamilah Almuqati; Mysara Alfaki; Ahmed Alkarani (Department of Nursing, Faculty of Medicine, Diponegoro University, 2023)
Background: Whenever an organisational change is mentioned in any research context, the uncertainty concept is usually mentioned as it is or as synonymous with lack of information, ineffective communication, and/or weak feedback. Since no previous studies have investigated the organisation’s readiness to change in Saudi Arabia, this study will provide empirical evidence regarding these critical components.Purpose: The study aimed to explore how healthcare providers in the Ministry of Health perceive the ministry’s readiness to change.Methods: A descriptive cross-sectional correlational design was used for this study. Three public hospitals under the Ministry of Health were involved in recruiting 420 healthcare providers using a convenient quota sampling. A personal data sheet and the organisational readiness for implementing change (ORIC) scale were used for data collection. ANOVA and t-tests were used to analyze the data.Results: The total response rate was 70%. The participants in the study perceived their organisation to be highly ready to change (3.76±0.73). The organisational readiness to change perceived by nurses (3.86+0.98) was significantly greater than that perceived by physicians (3.56+0.90) and allied healthcare providers (3.61+0.92), with a p-value of 0.001. In addition, the organisational readiness to change was significantly related to the participants’ specialty, age, experience, and gender (p<0.05).Conclusion: The findings showed that participants believed that their organisation was highly ready to change. Participants’ specialty, age, experience, and gender were significantly related to organisational readiness to change. This study recommends that leaders need to be proactive in managing changes by assessing the change readiness in their organisation and setting out plans to prepare the organisation.